Unveiling the dynamic connection: ICT, technological innovation, financial inclusion, natural resources, and environmental degradation in MENA countries: evidence from CS-ARDl and NARDL - Zhang, Henggang; Qamruzzaman, Md.; Monsur Mindia, Piana (Frontiers in Environmental Science, 2025)
Rapid urbanization, economic dependency on natural resources, and ecological damage are major obstacles to environmental sustainability in the Middle East and North Africa (MENA). This paper examines the dynamic interactions among Information and Communication Technology (ICT), technical innovation, financial inclusion, natural resource rent, and environmental sustainability using ecological footprints and load capacity factors as main indicators. The research finds linear and asymmetric correlations using panel data from 2001 to 2022 and sophisticated econometric approaches like Cross-sectionally Autoregressive Distributed Lag (CS-ARDL) and Nonlinear ARDL (NARDL) models. The results expose that by encouraging energy efficiency and sustainable resource use, ICT and technical innovation significantly help to reduce environmental damage. Financial inclusion, however, has two different effects: if not properly controlled, it may encourage unsustainable spending habits even while it helps to provide cash for green ventures. Moreover, natural resource rents greatly worsen environmental damage, supporting the resource curse theory, especially in areas with inadequate government systems. The asymmetry approach emphasizes the varied impacts of positive and negative shocks in ICT and technological innovation on sustainability, thus implying the need for customized policy responses. With a comprehensive view of sustainability in MENA and strong econometric modeling incorporating environmental, technical, and financial components, this paper adds to the body of knowledge. Emphasizing the requirement of legislative frameworks that support green funding, improve institutional quality, and stimulate the use of digital and clean technology, the findings provide policymakers with practical insights. Aligning economic resilience with environmental sustainability would depend mostly on strengthening governance and sustainable investment policies, guaranteeing long-term ecological and economic stability.